2021
DOI: 10.1111/jocd.14353
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the evidence level for the use of radiofrequency in aesthetic treatments: A systematic review and meta‐analysis

Abstract: Background Radiofrequency (RF) is a non‐invasive or minimally invasive procedure with a low risk of complications. It has been employed for several aesthetic purposes. Aim This study aimed to conduct a systematic literature review on the use of RF for aesthetic applications and assess the level of accumulated evidence for each condition. Methods Using the MEDLINE/PubMed and EMBASE databases, we searched for articles published from 2009 to 2019 describing the use of RF treatment for aesthetic purposes. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…8 AFL and MNRF have separately been shown to be effective in the treatment of acne scars, 15,23,27 although the evidence for MNRF is scarce. 13,26 Here, we have shown that AFL and MNRF can lead to similar outcomes. Our results are encouraging in clinical practice where access to certain devices is limited, or long wait-times can be mitigated by referring to either treatment modality.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…8 AFL and MNRF have separately been shown to be effective in the treatment of acne scars, 15,23,27 although the evidence for MNRF is scarce. 13,26 Here, we have shown that AFL and MNRF can lead to similar outcomes. Our results are encouraging in clinical practice where access to certain devices is limited, or long wait-times can be mitigated by referring to either treatment modality.…”
Section: Discussionmentioning
confidence: 65%
“…8,17,24 AFL and MNRF represent established and emerging energy-based treatments effective in treatment of acne scars. 8,13,14,26 To our knowledge, there are no randomized, controlled studies comparing AFL and MNRF for acne scars. Here, we aimed to compare the efficacy on skin texture in people with acne scars and differences in patient tolerability after a single AFL compared with a single MNRF treatment in a randomized, split-face trial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiofrequency (RF) is a commonly used treatment in the field of aesthetic medicine. 1 Unlike lasers, RF does not target specific chromophores by selective photo thermolysis. Instead, RF generates heat resulting from different tissue resistances to the electro-magnetic current.…”
Section: Introductionmentioning
confidence: 99%
“…RF technologies can be applied to any skin type through non-invasive or minimally invasive procedures and with minimal risk of complications or side effects [14]. RFs have been applied successfully for aesthetic treatments such as sagging skin, wrinkles, body / skin rejuvenation, treatments for facial expression lines, recent and late fibrosis, scars and adhesions, cellulite, localized fat and alopecia [15]. Within electrothermal RF therapies, Capacitive Resistive Electrical Transfer (CRET) is a noninvasive technology that applies 448 kHz currents and has been used successfully in the regeneration of both muscle tissue and bone, as well as tendons and ligaments [16][17][18].…”
Section: Introductionmentioning
confidence: 99%